Relapsing Polychondritis: Clinical Presentation, Diagnosis and Treatment Approaches - Stondzik, Gabriela; Garbacz, Anna Izabela; Majszyk, Tomasz Julian; Głuski, Jacek; Brzozowska, Agnieszka; Borowiecka, Patrycja; Węglarz, Aleksandra; Kosiorek, Paweł; Niezgoda, Ada; Olborska, Anna; et al. (Quality in Sport, 2026)
Background: Relapsing polychondritis (RP) is a rare, chronic inflammatory disease with a relapsing course that leads to damage of cartilage and other proteoglycan‑rich tissues. The variable multisystem presentation and the lack of specific laboratory markers may delay diagnosis, which can result in irreversible deformities and organ‑related complications. Aim: The aim of this paper was to summarise current evidence on the epidemiology, clinical presentation, diagnosis, monitoring, and treatment of RP, with attention to disease heterogeneity and emerging pathogenetic concepts. Materials and methods: This paper was prepared as a narrative literature review. Searches were conducted in PubMed and Scopus, including review articles, observational studies and clinically relevant case series. Results: RP most commonly affects the auricles, nose, and laryngo‑tracheo‑bronchial structures, but may also involve the eyes, inner ear, and cardiovascular system. Diagnosis is primarily clinical, supported by ancillary investigations and exclusion of mimicking conditions; in practice, classification criteria described in the literature are often used. Disease monitoring should include assessment of activity, irreversible damage, and patient functioning; a disease-specific activity index (e.g. RPDAI and RPDAM) may support follow‑up. Treatment is individualised and depends on severity and organ involvement; systemic glucocorticoids are the cornerstone, conventional immunosuppressants are used as steroid‑sparing therapy, and biologic therapies are considered in refractory cases. Conclusions: RP remains a major diagnostic and therapeutic challenge due to its rarity, heterogeneous phenotype, and limited availability of high‑quality clinical evidence. Early recognition, assessment of dominant organ involvement, regular monitoring, and multidisciplinary care are essential.